Clay-TiO\(_2\) Composite as a Sustainable Solution for Wastewater Treatment: A Case Study of the Marais Masay Lake of Madagascar - Mahandrimanana, Andrianainarivelo; Rado, Rasolomampianina; Lunard, Andriamirindramanana Herison (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
The main objective of this research is to show that the composite material, made from clay and particles of TiO2, appears to be effective in eliminating pollution from urban wastewater. The availability of a treatment device available to everyone is necessary. Indeed, the use of local products such as clay could be beneficial for the population. Physicochemical analysis (pH, conductivity, SS, turbidity, nitrate, phosphate and chloride levels, COD, BOD) and bacteriological analysis (ASR, fecal coliforms, fecal streptococci and Escherichia coli) have made it possible to assess the quality of treated waters. The model reduced the amount of physicochemical pollution of wastewater at the end of the treatment. The pH is between 6 and 9, the conductivity is reduced, it goes from 429.33 to 273 \(μ\)S/cm, the turbidity is 17.8 NTU, and the SS varies from 12.5 mg/l. Nitrite and phosphate levels are 0 mg/l. The COD is less than 50 mg/l, the BOD is less than 150 mg/l all values meet the release standard. Based on these results, 99.78% of Streptococci fecal germs, 99.64% of ASR, 97.84% of fecal coliforms, and 98.43% of Escherichia coli packages are eliminated. The mean value of the SS of the raw water to be analyzed is found to be greater than the value of the discharge water standards (<60mg/l), i.e., it has a high concentration and is therefore very rich in dissolved and colloidal materials. Microbiological and physicochemical analyses revealed that the treated waters are qualitatively improved. The treated water meets WHO (World Health Organization) standards. The number of germs decreased sharply after treatment with composite materials made from clay and TiO2, with the exception of ASR, which resisted the treatment. The values of physicochemical parameters such as turbidity, suspended solids (SS), nitrates, and chlorides were below standard levels. Various types of clay found in Madagascar can be utilized as a support of TiO2.